PERAN ORANG TUA ANAK PPA DALAM MENGEMBANGKAN KEHIDUPAN ROHANI ANAK PPA ID-127 USIA 9-11 TAHUN BERDASARKAN II TIMOTIUS 3:14-17. - Tilaar, Stenny (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Education is a very important need for every human. And one of the goals of education is so that children know how they live to grow up to be mature, independent and become useful members of society. Family education or education from parents is the first education that children receive because family is one of the most central and vital places for the process of education or teaching. Education is needed because many children have a bad life. The focus of the research is the role of parents in developing children's spiritual life based on II Timothy 3: 14-17. This study aims to find out how the role of Parents in developing children's spiritual life based on II Timothy 3: 14-16. In this case it guides and teaches about Jesus Christ and Salvation, declares mistakes, improves behavior, and educates in truth. The research method used is qualitative. Qualitative research does not carry out calculations but a research process that produces descriptive data in the form of written or oral words from people. The object of the research was the parents of PPA ID-127 children aged 9-11. The research results show that there are parents who teach Jesus Christ but occasionally, parents shift the responsibility to the church and some ignore their responsibilities.